Adsorption of bisphenol A by TiO2-based organic–inorganic hybrid materials. (October 2022) - Suzuki, Ukyo; Kameda, Tomohito; Kumagai, Shogo; Saito, Yuko; Yoshioka, Toshiaki
Abstract: In this study, TiO2 -P25 was modified with benzoic acid (BA) and 2-naphthalenecarboxylic acid (NCA), and subsequently used to adsorb bisphenol A (BPA). The relationship between the hydrophobicity of the modified TiO2 and the amount of BPA adsorbed was investigated. The equilibrium adsorption data were analyzed using the Langmuir, Freundlich, Dubinin–Radushkevich, Temkin, Harkins–Jura, and Halsey models. Additionally, TiO2 and Tix Zr(1- x ) O2 of high specific surface area were synthesized via the sol-gel and solvothermal methods. The materials were modified using NCA and used to adsorb BPA. The surface properties of the adsorbent were investigated by Brunauer–Emmett–Teller surface area analysis, Barrett–Joyner–Halenda pore size analysis, CO2 temperature-programmed desorption, and CHN elemental analysis. The specific surface area of Tix Zr(1- x ) O2 (252.1– 455.0 m 2 /g) was higher than that of TiO2 (157.6 m 2 /g) and the amount of NCA modified onto Tix Zr(1- x ) O2 (1.106– 1.319 mmol/g) was also higher than that of TiO2 (0.405 mmol/g). The amount of NCA modification onto Tix Zr(1- x ) O2 was promoted by surface base points. The maximum amount of BPA adsorbed was 22.4 mg/L, which was 5.86 times that of TiO2 -P25, and approximately 90 % of the BPA was removed from a solution having an initial concentration of 100 mg/L. Graphical abstract: Unlabelled Image Highlights: Removal of bisphenol A from water by organic-inorganic hybrid materials Adsorption mechanism of bisphenol A by carboxylic acid-modified TiO2 Large amount of carboxylic acid modified onto Tix Zr(1- x ) O2 Large amounts of bisphenol A adsorbed by carboxylic acid-modified Tix Zr(1- x ) O2 5.86 times increase in adsorption amount compared to TiO2 -P25